Autumn of the patriarch: the Pinochet extradition debacle and beyond—human rights clauses compared to traditional derivative protections such as double criminality. - Blakesley, Christopher L. (Journal of Criminal Law & Criminology)
The writer considers human-rights law and whether it plays a role in protecting individuals in the face of international extradition or other modes of international cooperation in criminal matters. He investigates the application of the traditional statist exemptions to extradition—an approach that is based on the concept that states are the only subjects of international law—and the approach that considers the individual to be a subject of international law, at least to a degree. He asserts that the struggle between these approaches highlights the tension between the value of protecting individual human rights in the criminal justice arena and the need to provide effective international law enforcement. He maintains that if impunity for crimes against humanity and war crimes is to be ended, it must be done in a way that is consistent with the highest protection of human-rights interests for those being prosecuted.